2015
DOI: 10.1016/j.oooo.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

World Workshop on Oral Medicine VI: Patient-reported outcome measures and oral mucosal disease: current status and future direction

Abstract: Objective: This systematic review aimed (i) to explore the Patient-Reported Outcome Measures (PROMs) currently used in the oral mucosal disease literature and to report on the type and context of the use of these instruments and (ii) to provide a future direction for PROMs in oral medicine practice and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 135 publications
0
30
0
5
Order By: Relevance
“…More recently, studies have included patient‐reported outcomes (PROs), typically self‐reports of pain severity using visual analogue scales (VAS; Thongprasom et al, ), or more detailed scoring systems, such as the Oral Disease Severity Score (ODSS; Escudier et al, ) and others (Piboonniyom, Treister, Pitiphat, & Woo, ). A few studies have incorporated a more detailed assessment of the impact of OLP on an individual's daily life through the inclusion of (oral) health‐related quality‐of‐life scales (Hegarty, Hodgson, Lewsey, & Porter, ; McGrath, Hegarty, Hodgson, & Porter, ; Ni Riordain et al, ). Recently, the Chronic Oral Mucosal Disease Questionnaire (COMDQ) was developed for use with chronic oral mucosal conditions, including OLP (Ni Riordain & McCreary, , ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have included patient‐reported outcomes (PROs), typically self‐reports of pain severity using visual analogue scales (VAS; Thongprasom et al, ), or more detailed scoring systems, such as the Oral Disease Severity Score (ODSS; Escudier et al, ) and others (Piboonniyom, Treister, Pitiphat, & Woo, ). A few studies have incorporated a more detailed assessment of the impact of OLP on an individual's daily life through the inclusion of (oral) health‐related quality‐of‐life scales (Hegarty, Hodgson, Lewsey, & Porter, ; McGrath, Hegarty, Hodgson, & Porter, ; Ni Riordain et al, ). Recently, the Chronic Oral Mucosal Disease Questionnaire (COMDQ) was developed for use with chronic oral mucosal conditions, including OLP (Ni Riordain & McCreary, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that previous studies have suggested that GSSS are effective in stimulating salivary secretion, to our knowledge very few studies have looked upon the effects of these products on PROs (Ní Ríordáin et al, ). In this study, however, interpreting the PROs must be done with caution since due to the bidirectional nature of scores, a simple comparison of aggregate answers may be insufficient to provide accurate information about the real meaning of the data (Tsakos et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…While a clinician‐centred RAS‐specific clinical scoring system is available (Tappuni, Kovacevic, Shirlaw, & Challacombe, ), very few studies have focussed upon the use and the quality properties of PROMs in patients with RAS. Three narrative reviews have reported on the use of PROMs in patients with a range of oral mucosal diseases (Ni Riordain & McCreary, ; Ni Riordain et al., ; Wiriyakijja, Fedele, Porter, Mercadante, & Ni Riordain, ). There remains, however, no critical assessment of the quality properties of PROMs in patients with RAS.…”
Section: Introductionmentioning
confidence: 99%